Managing patients with multimorbidity. (July 2018) - Feather, Adam
Abstract: Patients with multimorbidity or co-morbidity are becoming increasingly common in all UK health and social care settings. Assessment of such patients requires dedicated time and appropriate resources, coordinated and led by a trusted clinician who should act as the patient's advocate. A collaborative, multidisciplinary approach based around comprehensive geriatric assessment works best, with patients and their carers directing the aims and objectives. The future management and care of these patients will be influenced by increased investment and inclusion in research into this complex group, advances in medical science and information technology, and a focus by healthcare professionals on early prevention, rather than palliation later in people's lives.